After crisis: health, politics and reflections on the European refugee crisis. Issue 4 (2nd October 2019) - Abbas, Mustafa
ABSTRACT: The years 2014 and 2015 saw a dramatic rise in the number of migrants entering Europe via the Mediterranean. This rise was mostly accounted for by refugees fleeing the civil war in the Syrian Arab Republic. Since that time Europe has been gripped in a political and humanitarian crisis as the incoming numbers overwhelmed individual state and collective European Union ability to respond effectively. In this article, I explore the European Migrant Crisis in geographical, political and humanitarian perspectives, describing and explaining the key events of the crisis. I then go on to a study of the major health issues arising from the crisis in terms of communicable and non-communicable disease, mental health, gender-related health and access to healthcare. Finally, I discuss the global dimensions of the refugee crisis and enter into a discussion of the roles and effectiveness of the UNHCR and the European Union's response as a whole.